Psychological outcomes of low-dose CT lung cancer screening in a multisite demonstration screening pilot: the Lung Screen Uptake Trial (LSUT). Issue 12 (21st October 2020) - Kummer, Sonja; Waller, Jo; Ruparel, Mamta; Duffy, Stephen W; Janes, Samuel M; Quaife, Samantha L
Abstract : Background: Previous studies of psychological burden in low-dose CT (LDCT) lung cancer screening trials may lack generalisability due to participation bias and control arms having elevated distress. Methods: Current and former smokers (n=787, aged 60–75) within a real-world screening demonstration pilot completed measures of lung cancer worry at three time points (T0 : appointment, T1 : next day, T2 : 3 months) and anxiety and depression at two time points (T0 and T2 ). A 'screening unaware' community sample (n=383) with the same age and smoking characteristics completed these measures once (T0 ). Mean scores were compared by sample type and LDCT result. Results: Compared with the community sample (T0 ), mean scores were higher in the screening sample, and statistically significantly increased in adjusted analyses, for lung cancer worry at T0 and T2 (mean (M): 9.32; 95% CI 8.96 to 9.69 vs M: 11.34; 11.09 to 11.59 and M: 11.88; 11.49 to 12.27), for anxiety at T0 and T2 (M: 3.32; 2.94 to 3.70 vs M: 4.73; 4.42 to 5.04 and M: 5.78; 5.33 to 6.23) and depression at T2 (M: 3.85; 3.44 to 4.27 vs M: 4.15; 3.76 to 4.55). Scores were highest for those with indeterminate (eg, T2 anxiety M: 6.93; 5.65 to 8.21) and incidental findings (primary care follow-up M: 5.34; 4.67 to 6.02) and those ineligible for screening (M: 6.51; 5.25 to 7.77). Being female, younger, not in paid employment, not married/cohabiting with a partner and lower education predicted poorer psychological outcomes at T0, but not T2 after adjusting for baseline scores. Mean scores remained within 'normal' clinical ranges. Conclusion: Psychological distress was raised among high-risk individuals undergoing LDCT screening in a real-world setting, but overall differences were unlikely to be clinically meaningful. It will be critical to monitor the psychological impact of services longitudinally across diverse settings, including subgroups vulnerable to clinically elevated distress. Trial registration: The Lung Screen Uptake Trial was registered prospectively with the International Standard Registered Clinical/soCial sTudy (ISRCTN) (Number: ISRCTN21774741 ) on 23 September 2015 and the National Institutes of Health ClinicalTrials.gov database (NCT02558101 ) on 22 September 2015.